Venous Thromboembolism Prophylaxis and Screening: A Clinical Audit - Amir Hamza Khan, Amarah Nisar, Jawad Mabood, Hidayat Ullah (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: We aimed to audit venous thromboembolism in surgical patients at risk of VTE presented to surgical department in 2021 using the caprini risk assessment model. Methodology: This clinical audit was conducted in surgical D unit department of Surgery, Khyber Teaching Hospital, Peshawar from July 2021 to December 2021. A total of 150 patients each for the audit group and the re-audit group were selected through non-probability consecutive sampling for both genders. A predesigned proforma according to caprini risk assessment model was used to assess the patient’s individual risk for DVT and provision of appropriate prophylaxis. Data was entered into Microsoft excel, analyzed through SPSS version 23 and results were presented in the form of descriptive writing and tables. Results: The mean age of the study population was 50.47 with relatively equal selection from both genders. None of the patients in the audit group were properly grouped for their risk of DVT and management needed as mentioned in the caprini RAM guidelines. In the re-audit group, 100% of the patients were accurately categorized into groups and the VTE risk assessment percentage significantly improved from 0% to 80.8%. Conclusion: The audit showed noticeable deficiencies in record keeping and clinical assessment of VTE risk in the management of hospital patients. However, through appropriate measures this insufficiency can be amended with appreciable results.